Hematoxylin Bodies in Pediatric Bone Marrow Aspirates and their Utility in the Diagnosis of Systemic Lupus Erythematosus. (May 2018) - Xu, Min; Chisholm, Karen M; Fan, Guang; Stevens, Anne M; Rutledge, Joe C
In our recent case report, the finding of lupus erythematosus (LE) cells in a bone marrow aspirate led to the diagnosis of systemic lupus erythematosus (SLE) and appropriate treatment, although the patient was not clinically suspected to have SLE. To determine whether LE cells are present in the bone marrow aspirates of SLE patients, but overlooked in routine bone marrow morphology review, bone marrow aspirates from 30 pediatric patients (15 with SLE and 15 with other diagnoses) evaluated by rheumatologists were reviewed. LE cells were found in the bone marrow aspirates of only 1 SLE patient and none in non-SLE patients. However, hematoxylin bodies were identified in 53% (8/15) of SLE patients. Neither hematoxylin bodies nor LE cells were found in the aspirates from patients with other disorders. Three additional pediatric patients identified prospectively were found to have hematoxylin bodies in the bone marrow aspirates. Although the diagnosis was not initially suspected, 2 of the 3 patients were subsequently diagnosed with SLE. All patients with hematoxylin bodies and SLE had antinuclear antibody titers ≥1:640 with a homogeneous staining pattern. In addition, bone marrow aspirates of 9 adult patients were reviewed, and neither LE cells nor hematoxylin bodies were identified. In summary, hematoxylin bodies were present in the bone marrow aspirates of many pediatric SLE patients, while LE cells were rare. The finding of hematoxylin bodies in pediatric bone marrow aspirates is a helpful and specific diagnostic clue that may lead to the diagnosis of SLE when other clinical features are nonspecific.